Non-conventional practice versus evidence-based medicine. A scientific and ethical analysis of the Italian regulation - Patuzzo, Sara; Ciliberti, Rosagemma (Acta Biomedica Atenei Parmensis, 2017)
Background: The current lack of scientific validation of non-conventional treatments in medicine, whose epistemological foundations lie in scientific evidence and experimentation, raises significant questions regarding the costs and benefits of alternative-treatment forms. Nonetheless, in the last few decades non-conventional treatments have been increasingly recognised by the Italian medical profession, with one regional healthcare administration adopting some non-conventional practices as part of its conventional healthcare services.Aims: The Authors aim to analyse non-conventional treatments in medicine from an epistemological, cultural, ethical, political and economic point of view, in order to highlight criticalities and incongruities, especially when these treatments are approved by a public healthcare system, which should be grounded on the “evidence-based medicine” principle. Conclusions: Non-conventional treatments in medicine are constituted by meta-theories, i.e. philosophical, religious and ideological concepts that conflict with contemporary rational, empirical medicine. In the interest of patients and society, the paper stresses the incongruity of a healthcare system which, despite being grounded on the “evidence-based medicine” principle, allows the development of non conventional treatments. Having said that, medical science should address not only the biological domain of illness but also its existential implications. Awareness and respect for the individual experience can undoubtedly lead to a new medical model that allows for a more effective therapeutic intervention.